2008
DOI: 10.2337/dc07-0959
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes and Impaired Fasting Glucose in the Adult Population of Iran

Abstract: OBJECTIVE -Despite concerns regarding a diabetes epidemic in the Middle East, internationally published data on national estimates of prevalent type 2 diabetes in Iran do not exist. With this article, we document a dramatically high prevalence of diabetes in Iran. RESULTS -We found that 7.7% of adults aged 25-64 years, or 2 million adults, have diabetes, among whom one-half are undiagnosed. An additional 16.8%, or 4.4 million, of Iranian adults have impaired fasting glucose. RESEARCH DESIGN AND METHODSCONCLUSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
195
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(214 citation statements)
references
References 8 publications
(3 reference statements)
12
195
3
Order By: Relevance
“…The overall prevalence of IFG was lower than that reported for the US [26] and higher than the prevalence from an Indian study [27], being in range with recent studies on the population of Iran [28].…”
Section: Discussionsupporting
confidence: 71%
“…The overall prevalence of IFG was lower than that reported for the US [26] and higher than the prevalence from an Indian study [27], being in range with recent studies on the population of Iran [28].…”
Section: Discussionsupporting
confidence: 71%
“…We could not find any study investigating the results of drinking ST on diabetic complications including hypertension. [22][23][24] As the general perception in Iran and many other countries is in favour of drinking tea and the people know it as a safe herbal drug, also knowing that herbal drugs do not have the adverse reactions as chemical drugs have, this study was designed to assess the short-term effects of consuming ST infusion on BP in patients with type II diabetes and to compare it with those of black tea (BT). Regarding the chemical composition of ST, in this study our hypothesis was that drinking ST infusions, as is prescribed in traditional medicine, would effectively change the diabetic patients' BP.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity levels were not significantly associated with diabetes; however, this association has been supported by other studies. 8,14,28,29 Our future studies may need to assess physical activity using standardized data collection tools.…”
Section: Discussionmentioning
confidence: 99%
“…7 The study from Iran demonstrated that diabetes was more prevalent among older age groups, females, and urban dwellers. 8 In China, the prevalence of diabetes in the 35-74 age group was 5.5%, with 5.8% of females and 5.2% of males being diagnosed with diabetes. 9 A study in Pakistan found that central obesity, hypertension, and family history of the disease were risk factors for diabetes.…”
Section: Researchmentioning
confidence: 99%